Дослідження поліморфізму довжини інтронів генів ß-тубуліну у сортів Triticum aestivum L. та Hordeum vulgare L. - Рабоконь, А.М.; Демкович, А.Є.; Пірко, Я.В.; Блюм, Я.Б. (Фактори експериментальної еволюції організмів, 2015)
Aims. Tubulin-Based-Polimorphism (TBP) was originally introduced as a novel method for assaying genetic diversity in plants. In this connection, testing of this method in genetic research of cereals like as local wheat and barley varieties is very necessary. Methods. The CTAB-method for the isolation of DNA, PCR amplification, electrophoretic analysis under non-denaturing polyacrylamide gel and staining by silver nitrate method were used. Results. Genetic polymorphism of wheat and barley varieties was described on the basis of electrophoresis of TBP products. It was found that the number of the amplicons that correspond to the first intron of β-tubulin can be varying quite widely (94–3000 bp –Triticum aestivum L.; 97–1500 bp – Hordeum vulgare L.). Conclusions. Obtained data show that the intron length polymorphism method has good differentiating ability at least on some cereals. Thus, TBP – rapid, simple and reliable method that does not require much preliminary information about the genome of the object of interest; it can be useful in various genetic studies of plants.